(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the analysis of transformation of bolshevists’ opinions on the conception of proletarian state in conditions of First world war and revolutionary shocks of 1917-1921. The author from the newest methodological positions exposes the discussion in the environment of political elite of that time in relation to the prospects of development of the state and society.